Does wage rigidity really exist? New evidence from US panel data - Korbinian von Blanckenburg; Alexander Geist; Jörg Schmidt (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2009)
Downward nominal wage rigidity (DNWR) could prevent real wage adjustments in times of low inflation rates. Nominal wage rigidity based on annual wages can at least be reduced, if the number of working hours is considered. This leads to a lower degree of DNWR in hourly wage changes. In this paper, we use a histogram-location approach to investigate to what extent annual as well as hourly wages are subject to downward nominal wage rigidity. Using data from the Panel Study of Income Dynamics (PSID) we find that annual wage changes exhibit a substantially higher level of wage rigidity than hourly wage changes which also holds for males compared to females.
Keywords: E24; J30; J31; 330; Wage Rigidity; Histogram-Location Approach